2009
DOI: 10.1007/s12207-009-9055-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Injustice is Associated with Heightened Pain Behavior and Disability in Individuals with Whiplash Injuries

Abstract: The present study examined the relationship between perceived injustice associated with whiplash injury and displays of pain behavior. Individuals (N=85) with whiplash injuries were filmed while performing a simulated occupational lifting task. They were also asked to complete measures of pain, perceived injustice, catastrophic thinking, depression, and functional disability. Consistent with previous research, high levels of perceived injustice were associated with more intense pain, higher levels of catastrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
96
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 53 publications
13
96
2
4
Order By: Relevance
“…Accordingly, our findings extend the growing body of research regarding known correlates of perceived injustice. Given the previously demonstrated associations between perceived injustice and variables associated with pain and disability (including pain catastrophizing and pain-related fear [26,38,39,41]), this finding is perhaps not surprising, as these constructs/cognitions also show association with AB (e.g., [1,18,45,56]). Although this was not directly assessed in the current study, it is important to note that previous research acknowledges some overlap between perceived injustice and pain catastrophizing [38]; however, perceived injustice has been conceptualized (and supported) as a distinct construct reflecting elements of blame and anger, which are not captured by pain catastrophizing [29,38,55].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Accordingly, our findings extend the growing body of research regarding known correlates of perceived injustice. Given the previously demonstrated associations between perceived injustice and variables associated with pain and disability (including pain catastrophizing and pain-related fear [26,38,39,41]), this finding is perhaps not surprising, as these constructs/cognitions also show association with AB (e.g., [1,18,45,56]). Although this was not directly assessed in the current study, it is important to note that previous research acknowledges some overlap between perceived injustice and pain catastrophizing [38]; however, perceived injustice has been conceptualized (and supported) as a distinct construct reflecting elements of blame and anger, which are not captured by pain catastrophizing [29,38,55].…”
Section: Discussionmentioning
confidence: 62%
“…However, in contrast to these studies, no association was observed between perceived injustice and pain intensity ratings; the effect was confined to ratings of anger and sadness. With respect to ratings of sadness, the association between perceived injustice and depression is well documented [26,30,31,38,39,41]. Further, a recent study by Scott and colleagues pointed to the association of perceived injustice with various indices of anger [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Franche et al (2009) present research on the development of an assessment tool of perceived injustice and the relationship of scores obtained with the instrument to heightened pain behavior and disability. Second, Sullivan et al (2009) undertook empirical investigation of the pain elicited by putting forth effort on physical tasks and scores on a different scale of perceived injustice. Third, in a legal paper, Hayman (2009) explores jurisprudence and emerging legal issues related to damages for mental distress and bad faith in disability claims.…”
Section: Fairness and Justice Issues In Disability Claims: Psychologimentioning
confidence: 99%
“…The study by Sullivan et al (2009) uses a different measure of perceived justice and reveals that individuals with elevated levels of perceived injustice displayed more protective pain behaviors than individuals with low levels of perceived injustice, regardless of physical task demands. Like Franche et al (2009), the authors of this study postulate the importance of evaluating perceived injustice as one of the key predictors of disability and potential targets for interventions.…”
Section: Fairness and Justice Issues In Disability Claims: Psychologimentioning
confidence: 99%